I alone can fix it : Donald J. Trump's catastrophic final year - Leonnig, Carol; Rucker, Philip (New York : Penguin Press, 2021)
"The true story of what took place in Donald Trump's White House during a disastrous 2020 has never before been told in full. What was really going on around the president, as the government failed to contain the coronavirus and over half a million Americans perished? Who was influencing Trump after he refused to concede an election he had clearly lost and spread lies about election fraud? To answer these questions, Phil Rucker and Carol Leonnig reveal a dysfunctional and bumbling presidency's inner workings in unprecedented, stunning detail"--
Deadly distractions -- Totally under control -- Seeking revenge -- The P-word -- Rebelling against the experts -- Refusing to mask up -- Bunkers, blasts, and bibles -- Staring down the dragon -- A sea of empty seats -- The skunks at the picnic -- Fear and fantasy -- Self-sabotage -- Stand back and stand by -- Nobody's immune -- Somebody's crazy uncle -- The reckoning -- The big lie -- Strange rangers -- Cries of injustice -- Hitting a dead end -- The insurrection -- Landing the bad boy -- Epilogue.
Includes bibliographical references and index.
Keywords: Trump, Donald, -- 1946-; Trump, Donald, -- 1946-; 2017-2021; COVID-19 Pandemic, 2020-; COVID-19 (Disease) -- Political aspects -- United States; Presidents -- United States -- Election -- 2020.; POLITICAL SCIENCE / American Government / Executive Branch; POLITICAL SCIENCE / American Government / National; POLITICAL SCIENCE / Corruption & Misconduct; Politics and government; United States -- Politics and government -- 2017-2021.; United States